Gold catalysis: in situ EXAFS study of homogeneous oxidative esterification - Hashmi, A. Stephen K.; Lothschütz, Christian; Ackermann, Martin; Döpp, René; Anantharaman, Sankaran; Marchetti, Benjamin; Bertagnolli, Helmut; Rominger, Frank (Chemistry - a European journal, 2010)
Gold complexes were prepared and investigated as catalysts for the oxidative esterification of aldehydes. Stabilisation by pyridine ligands gave good conversions and the in situ extended X-ray absorption fine structure (EXAFS) study of the reactions indicated that the reaction mixtures contained only mononuclear gold species. Thus, this is the first proof for a homogeneous gold-catalysed oxidation reaction; the presence of nanoparticles could be excluded experimentally.
First published: 12 July 2010
Gesehen am 27.03.2023